Intertextuality novel kcb 2 habiburrahman el shirazy with novel ksz & z taufiqurrahman al azizy - Kurniawati, Masrah; Misriani, Misriani; Fitriani, Yessi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
The literary works that appear are not necessarily the work of the Authors, but they have read previous literary works. This study aims to determine intertextuality by looking at the similarities and differences in the novel Ketika Cinta Bertasbih 2 by Habiburrahman El Shirazy with the novel Kidung Shalawat Zaki and Zulfa by Taufiqurrahman Al Azizy using a qualitative descriptive method. Intertextuality plays a role in seeing a work that can be the basis for the creation of another work. The data sources of this research are Novel Ketika Cinta Bertasbih 2 by Habiburrahman El Shirazy published in 2007 and Kidung Shalawat Zaki and Zulfa by Taufiqurrahman Al Azizy in 2010. This research shows that intertextual occurs in the novel Ketika Cinta Bertasbih 2 by Habiburrahman El Shirazy with Song Shalawat Zaki and Zulfa by Taufiqurrahman Al Azizy because the theme, plot, setting, and message tend to be the same. The intertextuality of these two novels also has differences as the creativity of their respective authors. The research of these two novels can be deepened further so that the intertextual relationship between the two becomes clearer.